The importance of retesting borderline results in COVID-19 diagnostics - Grego, Edita M.; Gospodinović, Hristina A.; S. Pavlović, Ljiljana; Jovanović, Verica S. (International Journal Of Community Medicine And Public Health, 2022)
The first case of COVID-19 in the Republic of Serbia was registered on 6 March 2020 based on data from the Ministry of Health of the Republic of Serbia.RT-PCR (real-time reverse transcription polymerase chain reaction) is the gold standard for detection for many infective agents. SARS-CoV-2 (human coronavirus 2019) comprises genes coding four basic structural proteins (E, M, N and S) and ORF1a and ORF1b genes coding two polyproteins. These genes represent targets for virus detection and the platform for RT-PCR test design.